Malabar Cements Limited: A Successful Employer in the Indian Cement Industry - Sivaramakrishnan, G.; I., Mohammad Sulaiman (Indian Journal of Marketing, 2012)
Prior to independence, there were few public sector enterprises in the country. In 1947, India was mainly an agrarian economy with a weak industrial base. The 1956 industrial policy resolution, a key facet of the Nehruvian socialistic system of mixed economy, gave primacy to the role of the state as the conscientious for industrial development and later, the strategies for public sector were outlined in 1973. Malabar Cements Limited (MCL) is a model company among the public sector organizations in Kerala. The noble causes of public sectors units are to uphold the industrial advancement in the state, but without forgetting the environmental and social obligations to attain. There is insalubrious competition in the cement market from private sector giants, resulting in inflating the cost of one of the fundamental construction materials mandatory for any modern engineering edifice. However, MCL is committed to the environment by keeping the atmospheric emission levels far below the prescribed norms fixed by the Pollution Control Boards. Over and above, the company is well aware of its responsibility to provide maximum employment to the people of the state and to take part in the social upliftment activities of the people.